Financial Technology Adoption and Digitization of Zakat Payment Behavior (ZISWAF: Jurnal Zakat dan Wakaf, 2023)
This research aims to examine the influence of digitization on zakat, with the  goal  of  understanding  the  motivation  to  shift  from  conventional  payment methods to digital alternatives. The alteration of Unified Theory of Acceptance and Use of Technology 2 (UTAUT) is selected by integrating perceived risk and trust. The analytic method is Partial Least Squares, with a sample size of 348 muzakki (zakat givers) observed.  The  results showthat theunderlying  factors  have  a considerable influence on  the  development  of  behavioral  intention,  with  trust playing a dual role by moderating and mediating theinteractions. These emphasize the  necessity  for  regulators  to  continuously  promote  technological  adaptability, develop  sufficient  infrastructure,  and  improve  digital  literacy  in  the  community. Moreover, thesteps enhance the possibility for national zakat collection, leading to the equitable distribution of wealth